Evaluación de la viabilidad de la implementación de tecnologías through tubing rotary drilling y coiled tubing drilling para la perforación de side tracks tipo slim hole en Colombia (2019)
This undergraduate dissertation covers a evaluation of the Through Tubing Drilling (TTD) technologies. First, a contextualization was carried out, summarizing their functionality, the advantages and limitations that they entail, basic components, and reference cases that demonstrate their applicability. In addition, the parameters of the mechanics of its implementation are detailed, exposing the theory on which the subsequent approaches were based. Next, a planning scheme for a TTD operation was established, consisting of the phases to follow the procedure. In this, in addition to presenting the design criteria, the variables whose simulation should be run were proposed, in order to estimate the drilling requirements of this type of well. This scheme was theoretically implemented in a study well "A", for which the corresponding simulations were run.